Sexual dysfunction in selective serotonin reuptake inhibitors receiving patients attending psychiatric outpatient department at tertiary level hospital in Pokhara: a cross sectional study (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Sexual dysfunction is common following treatment with selective serotonin reuptake inhibitors (SSRI) and can have a negative impact on treatment adherence. However, few patients spontaneously report these dysfunctions in clinical settings. The aim of this study was to find out the proportion and pattern of sexual dysfunction following treatment with SSRI.Method: A descriptive cross-sectional study was done in a tertiary level hospital among psychiatric patients visiting the outpatient department from 9 Nov 2022 to 8 Nov 2023, after receiving ethical approval from the institutional review committee. Demographic details, psychiatric diagnosis, medication used, and duration of medication used were recorded. The Depression, Anxiety, and Stress-21 Scale was used to assess depression, anxiety and stress and the psychotrophic related sexual dysfunction questionnaire was used to assess sexual dysfunction and its pattern.Result: A total of 87 patients receiving SSRI were included in the study. The proportion of sexual dysfunction among SSRI recipients was found to be 27(31.03%). The proportion of sexual dysfunction was higher in males 19(70.37%). Among those 27 patients, the most common pattern was decreased libido 17(62.96%), and vaginal lubrication 3(11.11%) was the least common pattern of sexual dysfunction. Out of 27 patients with sexual dysfunction 9(33%) spontaneously reported sexual dysfunction.Conclusion: Nearly one-third of recipients of SSRIs have sexual dysfunction, majority of patients may not report sexual dysfunction spontaneously and sexual dysfunction is seen more in paroxetine recipients.